2016
DOI: 10.3390/en9040296
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Analysis and Three-Dimensional Redesign of a Multi-Stage Axial Flow Compressor

Abstract: This paper describes the introduction of three-dimension (3-D) blade designs into a 5-stage axial compressor with multi-stage computational fluid dynamic (CFD) methods. Prior to a redesign, a validation study is conducted for the overall performance and flow details based on full-scale test data, proving that the multi-stage CFD applied is a relatively reliable tool for the analysis of the follow-up redesign. Furthermore, at the near stall point, the aerodynamic analysis demonstrates that significant separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In particular, the five-stage compressor's designed total pressure ratio approached the plan goal and exceeded the design goal with its stability margin. Ning et al [5] carried on an aerodynamic analysis and a three-dimensional (3D) redesign of a multi-stage axial flow compressor. The study discusses implementation of 3D blade design with multi-stage computational fluid dynamics methods towards a five-stage axial compressor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, the five-stage compressor's designed total pressure ratio approached the plan goal and exceeded the design goal with its stability margin. Ning et al [5] carried on an aerodynamic analysis and a three-dimensional (3D) redesign of a multi-stage axial flow compressor. The study discusses implementation of 3D blade design with multi-stage computational fluid dynamics methods towards a five-stage axial compressor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research is collaboration between the authors and EGAT to sustainably solve the problem. Many researchers including Ning et al [1] studied the aerodynamic analysis of the new multi-stage axial flow compressor. The results showed that large separation in the suction side of the last stator and the mainstream flow was the main factor that caused the loss.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that large separation in the suction side of the last stator and the mainstream flow was the main factor that caused the loss. The most significant achievement of the three-dimensional (3D) blade redesign in [1] was the stall margin improvement, which totaled around 13% of stall margin when compared to the baseline, while maintaining efficiency at the design points. Bian et al [2] investigated edge geometry with different blade parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Andrei [8] utilized 4 turbulence models in order to model a two-dimensional (2D) high loaded rotating cascade of an axial compressor and predict the lift and drag coefficients. Ning et al [9] implemented RANS equations with the use of the Spalart-Almaras one equation turbulence model focusing on the three-dimensional (3D) aerodynamic redesign of a 5-stage compressor with multi stage CFD methods. Menter and Langtry [10] presented a detailed study regarding the turbulence modelling approaches for the accurate prediction of the flow development in turbomachinery.…”
Section: Introductionmentioning
confidence: 99%